Impact of exposure to urban air pollution on grey squirrel (Sciurus carolinensis) lung health. (1st June 2023) - Torres-Blas, Irene; Horsler, Helen; Paredes, Ursula M.; Perkins, Matthew; Priestnall, Simon L.; Brekke, Patricia
Abstract: The increased rate of global urbanisation has recently exacerbated the significant public health problem of traffic related air pollution. Despite the known significant impact on human health, little is known about the effects of air pollution on wildlife health. The lung is the primary target organ for the effects of exposure to air pollution, leading to lung inflammation, altering the lung epigenome, culminating in respiratory disease. In this study, we aimed to assess lung health and DNA methylation profiles in Eastern grey squirrel ( Sciurus carolinensis ) populations living across an urban-rural air pollution gradient. Squirrel lung health was assessed in four populations situated across the most polluted inner-city boroughs to the less polluted edges of Greater London. We also assessed lung DNA methylation across three London sites and a further two rural sites in Sussex and North Wales. Lung and tracheal diseases were present in 28% and 13% of the squirrels respectively. Specifically, focal inflammation (13%), focal macrophages with vacuolated cytoplasm (3%) and endogenous lipid pneumonia (3%). There was no significant difference in prevalence of lung, tracheal diseases, anthracosis (carbon presence) or lung DNA methylation levels between urban sites and urban and rural sites respectively or NO2 levels. BALT (Bronchus-Associated Lymphoid Tissue) was significantly smaller in the site with highest NO2 and contained the highest carbon loading compared to sites with lower NO2, however differences in carbon loading in between sites were not significant. High pollution site individuals also had significantly higher numbers of alveolar macrophages which suggests that grey squirrels are exposed to and respond to traffic-related air pollution and further research is needed to understand the impact of traffic-related air pollutants on wildlife health. Graphical abstract: Image 1 Highlights: Urban squirrel populations in London have a high prevalence of respiratory diseases. No significant difference in disease between London populations within the city. High air pollution exposure populations had more alveolar macrophages. High pollution exposure populations had smaller BALT with higher carbon load. Global lung DNA methylation did not vary between urban and rural populations.